Three-dimensional optical tomographic imaging of breast in a human subject. - Huabei Jiang (IEEE Transactions on medical imaging)
We present for the first time a full three-dimensional (3-D) reconstruction of absorption images of breast from continuous-wave (cw) measurements performed on a premenopausal woman. Our 3-D optical images clearly reveal a large primary tumor as well as a small secondary tumor in a separate location of the breast. The multiple tumors identified by our 3-D optical imaging have been confirmed by the subsequent biopsy examination of the breast. Quantitative information of the optical images obtained is provided in terms of the location, size, and absorption coefficient of the tumors.